A cell-penetrating ARF peptide inhibitor of FoxM1 in mouse hepatocellular carcinoma treatment - Galina A. Gusarova; I-Ching Wang; Michael L. Major; Vladimir V. Kalinichenko; Timothy Ackerson; Vladimir Petrovic; Robert H. Costa (The Journal of Clinical Investigation, 2007)
The forkhead box m1 (Foxm1) transcription factor is essential for initiation of carcinogen-induced liver tumors; however, whether FoxM1 constitutes a therapeutic target for liver cancer treatment remains unknown. In this study, we used diethylnitrosamine/phenobarbital treatment to induce hepatocellular carcinomas (HCCs) in either WT mice or Arf–/–Rosa26-FoxM1b Tg mice, in which forkhead box M1b (FoxM1b) is overexpressed and alternative reading frame (ARF) inhibition of FoxM1 transcriptional activity is eliminated. To pharmacologically reduce FoxM1 activity in HCCs, we subjected these HCC-bearing mice to daily injections of a cell-penetrating ARF26–44 peptide inhibitor of FoxM1 function. After 4 weeks of this treatment, HCC regions displayed reduced tumor cell proliferation and angiogenesis and a significant increase in apoptosis within the HCC region but not in the adjacent normal liver tissue. ARF peptide treatment also induced apoptosis of several distinct human hepatoma cell lines, which correlated with reduced protein levels of the mitotic regulatory genes encoding polo-like kinase 1, aurora B kinase, and survivin, all of which are transcriptional targets of FoxM1 that are highly expressed in cancer cells and function to prevent apoptosis. These studies indicate that ARF peptide treatment is an effective therapeutic approach to limit proliferation and induce apoptosis of liver cancer cells in vivo.